Editorial: From Exceptional Cases to Everyday Abuses: Labour exploitation in the global economy - Quirk, Joel; Robinson, Caroline; Thibos, Cameron (Anti-Trafficking Review, 2020)
This article introduces a special issue on economic systems and everyday abuses of labour rights. In recent decades, neoliberal policies have transformed both the world economy and the world of work. Hard-won rights and protections have been eroded by deregulation, outsourcing, and subcontracting. New forms of unstable, isolated, and insecure work have emerged. This introduction examines the driving forces behind the increasing prominence of precarious work, the accelerating role of migrant labour within global economic systems, and the political relationship between everyday abuses and forms of severe exploitation which have recently come to be defined as human trafficking and modern slavery. We argue that a singular focus upon individual cases of extreme exploitation is unlikely to be effective, and can also draw attention away from the larger systems, interests, and abuses that are associated with the smooth and regular operations of the global economy. We also suggest that at least some of the energies which have recently been expended debating the contentious category of ‘modern slavery’ could be usefully redirected towards lower profile interventions concerned with worker and migrant rights. There are never going to be simple or straightforward solutions to labour abuses, so it is necessary to take many bumpy paths simultaneously, with small steps forward and some steps backward.